Spontaneous Complete Regression of Colon Cancer Liver Metastases in a Lung Transplant Patient: A Case Report. (12th January 2023) - Zwart, Koen; Ruigrok, Dieuwertje; de Graaf-Bos, Magda; Goldschmeding, Roel; Koopman, Miriam; Bol, Guus M.
Abstract : Background. Cancer has become an important cause of death in solid organ transplant patients. The cause of malignancies in patients with solid organ transplants is multifactorial, but the use of intensive immunosuppression is regarded as an important factor. We describe the spontaneous, complete regression of colon cancer liver metastases, without initiation of antitumor therapy, in a solid organ transplant patient after modulation of immunosuppressants. Case Presentation. A 59-year-old female was admitted with fever, general discomfort, and elevated liver enzymes. She had received a single lung transplant, five years prior, for end-stage chronic obstructive pulmonary disease. Abdominal ultrasound and a computed tomography scan showed extensive liver lesions, and liver biopsy determined that the lesions were liver metastases originating from a colonic adenocarcinoma. Histopathologic analysis revealed that the primary tumor and liver metastases were mismatch repair-deficient (BRAF V600E mutant and MLH1/PMS2-deficient), also known as a microsatellite instable tumor. The patient's clinical condition deteriorated rapidly, and she was discharged home with palliative care. No antitumor treatment was initiated. Additionally, there was a short period without any immunosuppressants. Unexpectedly, her clinical condition improved, and complete regression of liver metastases was observed on imaging two months later. Unfortunately, the patient developed rejection of her lung transplant and succumbed to pulmonary disease six months following her cancer diagnosis. The autopsy confirmed the primary colon tumor location and complete regression of >40 liver metastases. Conclusions. Disinhibition and reset of the host immune response could have led to immune destruction of the liver metastases of this patient's immunogenic dMMR colon carcinoma. This case underscores the huge impact that temporary relief from immunosuppressive therapy could have on tumor homeostasis. Balanced management of care for organ transplant recipients with malignancies requires a multidisciplinary approach involving medical oncologists and transplant physicians to reach the best quality of care in these complex cases.